Synthetic Bone Blocks Produced by Additive Manufacturing in the Repair of Critical Bone Defects - Muñoz, Eladio; Loyola, Ana Carolina; Pitol-Palin, Leticia [UNESP]; Okamoto, Roberta [UNESP]; Shibli, Jamil; Messora, Michel; Novaes, Arthur Belém; Scombatti de Souza, Sergio (SAGE Publications, 2024)
This study evaluated the efficacy of synthetic bone blocks, composed of hydroxyapatite (HA) or β-tricalcium phosphate (B-TCP), which were produced by additive manufacturing and used for the repair of critical size bone defects (CSDs) in rat calvaria. Sixty rats were divided into five groups (n = 12): blood clot (CONTROL), 3D-printed HA (HA), 3D-printed β-TCP (B-TCP), 3D-printed HA + autologous micrograft (HA+RIG), and 3D-printed β-TCP + autologous micrograft (B-TCP+RIG). CSDs were surgically created in the parietal bone and treated with the respective biomaterials. The animals were euthanized at 30 and 60 days postsurgery for microcomputed tomography (micro-CT) histomorphometric, and immunohistochemical analysis to assess new bone formation. Micro-CT analysis showed that both biomaterials were incorporated into the animals’ calvaria. The HA+RIG group, especially at 60 days, exhibited a significant increase in bone formation compared with the control. The use of 3D-printed bioceramics resulted in thinner trabeculae but a higher number of trabeculae compared with the control. Histomorphometric analysis showed bone islands in close contact with the B-TCP and HA blocks at 30 days. The HA blocks (HA and HA+RIG groups) showed statistically higher new bone formation values with further improvement when autologous micrografts were included. Immunohistochemical analysis showed the expression of bone repair proteins. At 30 days, the HA+RIG group had moderate Osteopontin (OPN) staining, indicating that the repair process had started, whereas other groups showed no staining. At 60 days, the HA+RIG group showed slight staining, similar to that of the control. Osteocalcin (OCN) staining, indicating osteoblastic activity, showed moderate expression in the HA and HA+RIG groups at 30 days, with slight expression in the B-TCP and B-TCP+RIG groups. The combination of HA blocks with autologous micrografts significantly enhanced bone repair, suggesting that the presence of progenitor cells and growth factors in the micrografts contributed to the improved outcomes. It was concluded that 3D-printed bone substitute blocks, associated with autologous micrografts, are highly effective in promoting bone repair in CSDs in rat calvaria.
Keywords: 3D-printed scaffolds; additive manufacture; bone regeneration; hydroxyapatite; β-tricalcium phosphate